Critical Thinking and Everyday Problem Based Learning - Carlos Saiz Sánchez; Silvia Fernández Rivas (Universitat Politècnica de València, 2012)
Critical thinking can be improved if accompanied by some methodologies like problem-based learning (PBL). We have developed a program to teach / learn to think where we have incorporated this technique. We applied this program to group of college students with very satisfactory results as regards academic performance. We have also used a test of critical thinking (PENCRISAL) to measure changes before and after instruction. The results have also been reasonably good and meaningful. Academic performance improved significantly, and we verified this improvement along the whole process of continuous assessment that we carried out. The fundamental dimensions instructed are five: deduction, induction, practical reasoning, decision making and problem solving. The comparison of performance in the PENCRISAL test has shown significant differences in all dimensions when comparing pre- with post- scores. The dimensions of the test are the same as those worked during instruction and cited above. In these five dimensions, there have been significant changes in the post-treatment measure. In the future, we will include some modifications in the program of instruction and assessment methodology. These changes are the result of the experience gained in this study.